Sistem Pakar Diagnosa dan Troubleshooting Kerusakan Website Menggunakan Metode Dempster-Shafer - Yusuf Hendra Pratama; Firmansyah Firmansyah (Jurnal Bumigora Information Technology (BITe), 2023)
Background: Website troubleshooting is the process of identifying, analyzing, and solving a website’s problems. The problem in this study is the lack of information and the length of time in knowing the website damage, so users have difficulty troubleshooting. Objective: The purpose of the research is to create an expert system that can be used to diagnose website damage and is easily accessible. Methods: The method used in this research was the Dempster-Shafer method, which is a method of proof based on the belief function and plausible reasoning in combining evidence to calculate the probability of damage to the website. Result: The results of this study were an expert system for diagnosing website crashes which had 15 symptoms and 5 crashes. The developed system showed an accuracy value of 84% with a trial run of 25 cases. Conclusion: The resulting expert system can be used to diagnose website damage based on symptoms with a good degree of accuracy.